The role of soil redox conditions in microbial phosphorus cycling in humid tropical forests - Avner Gross; Yang Lin; Peter K. Weber; Jennifer Pett‐Ridge; Whendee L. Silver (Ecology, 2020)
Humid tropical forests are among the most productive ecosystems globally, yet they often occur on soils with high phosphorus (P) sorption capacity, lowering P availability to biota. Short‐term anoxic events are thought to release sorbed P and enhance its acquisition by soil microbes. However, the actual effects of anoxic conditions on microbial P acquisition in humid tropical forest soils are surprisingly poorly studied. We used laboratory incubations of bulk soils, NanoSIMS analysis of single microbial cells, and landscape‐scale measurements in the Luquillo Experimental Forest (LEF), Puerto Rico to test the hypothesis that anoxic conditions increase microbial P acquisition in humid tropical forests. In laboratory and field experiments, we found that microbial P uptake generally decreased under anoxic conditions, leading to high microbial carbon (C) to P ratios in anoxic soils. The decreased P acquisition under anoxic conditions was correlated with lower microbial C use efficiency (CUE), an index of microbial energy transfer in ecosystems. Phosphorus amendments to anoxic soils led to increased microbial P uptake and higher CUE suggesting that microbes were less able to access and utilize P under natural low redox conditions. Under oxic conditions, microbial C:P ratios and CUE did not respond to changes in substrate stoichiometry. These results challenge the existing paradigm by showing that anoxic conditions can decrease microbial P uptake and ultimately constrain microbial CUE. Our findings indicate that soil redox conditions tightly couple soil P and C cycles and advance our understanding of controls on P cycling in humid tropical forest ecosystems.